DESIGN AND ANALYSIS OF THE KOMATSU PC400 EXCAVATOR'S TOOTH BUCKET THICKNESS USING THE FINITE ELEMENT METHOD - Sutrisna, Sutrisna; Prasetiyo, Angger Bagus; Juniar , Fatur Rizki Anggun (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Bucket teeth are an important component of an excavator that functions as a material penetrator or digger. This part is prone to failure because it is in direct contact with the ground. This study aims to determine the value of stress, strain, deformation, and safety factors that occur in the Komatsu PC400 excavator bucket teeth against thickness variations of 2.5 mm, 5 mm, 7.5 mm, and 10 mm. This study uses a computer with specifications: processor: Intel (R) Celeron (R) N4000 CPU @ 1.10 GHz, memory: 8 GB. Windows 10 Home Single Language 64-bit Operating System. This computer is equipped with Autodesk Inventor Professional 2023 and ANSYS Workbench R1 2023 software. The method used in this research is a testing method using ANSYS software with a finite element method approach, namely static structural. The simulation results of bucket teeth show the maximum deformation values are 0.16382 mm, 0.13832 mm, 0.1249 mm, and 0.11619 mm, respectively. Furthermore, the maximum equivalent stress values are 108.6 Mpa, 79.712 Mpa, 80.338 Mpa, and 79.992 Mpa, respectively. For the equivalent elastic strain maximum, 0.00052993, 0.00038899, 0.000392, and 0.00039029 were obtained. Then the safety factor value is obtained 3.8214, 5.2062, 5.1657, and 5.188. This shows that the thicker the thickness variation, the better the strength value.